A Newer World : Politics, Money, Technology, and What's Really Being Done to Solve the Climate Crisis - Hewitt, William F. (Book collections on Project MUSE., 2012)
This is an environmentalist's exploration of how we are bringing ourselves to the beginning of the end of the climate crisis and to the verge of sustainability. It is the story of the developments, trends, and visionary people that are, in many ways, mitigating the climate crisis and turning sustainable development into reality, not just a grand concept. Here the author explores the advances in business and finance, politics, design, science, and engineering that are transforming the world around us right now, even as the dire climatic consequences of the industrialization of our economies have become ever more starkly apparent. The received wisdom is that we are on an irrevocable path toward climate catastrophe. The political process, we are told, is broken. Coal-fired power plants in China and India are going to inundate the climate system with carbon dioxide before we can convert to less dangerous ways to generate power. Market mechanisms to control emissions have not, as yet, realized their potential. There is some truth in all of this, but it is not, by any means, the whole story. The book surveys the quantum leaps that are being made in clean technology and tells how governments, industry, and financial institutions are moving faster and more vigorously every day toward embracing these technologies. The challenges are real. This book tells the story of the major progress already being made in addressing the looming climate crisis.